Visual Studio 2010-Based Medical Records Completeness Information System Design - Henawati Priatna; Adha Nur Alawiya Makmun; Yuda Syahidin; Meira Hidayati (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
This study aims to find out the design of information analysis system completeness of filling medical records sheets by using Microsoft Visual Studio.NET 2010 Hospital X. Research method used is qualitative method with descriptive approach, while the method of developing data collection techniques used is waterfall method. The results of the research conducted found problems that are standard operating procedures related to filling medical records that have been established but in the implementation has not gone well, The management of data analysis completeness of filling medical records sheet is still using manual, There are still unfilled and incomplete medical records. The advice given is to build an effective and integrated information system, Implement a complete information system filling medical records sheets, Give advice to doctors or health workers to always complete medical records. The research results conclude that the standard of operational procedures (SOP) related to the completeness of filling medical records already exists but the implementation has not gone well. Analysis of medical records is still done manually, as well as in the creation of a report recapitulating the completeness of medical records. By implementing a completeness analysis system following the SOP that has been established by the hospital and building the design of a computerized information system to facilitate the analysis of the completeness of medical records filling sheets in Hospital X.